NILAI-NILAI MORAL DALAM PEMBELAJARAN ANAK USIA DINI DENGAN GAME EDUKASI CULLEN ABC?óÔé¼Ôäós BAGI GURU-GURU PAUD DI KECAMATAN TEMBALANG SEMARANG - Subur Laksmono Wardoyo; Ghufron Abdullah; Ririn Ambarini; Sari Kusumaningrum (Universitas PGRI Semarang, 2014)
Abstract Science and technology?é?á transferred to the?é?á teachers of early childhood education in?é?á Tembalang Semarang?é?á are the training how to apply the moral values ?óÔé¼ÔÇ??óÔé¼ÔÇ?in the learning for early childhood and?é?á the?é?á use of software Cullen ABC 's as teaching aids for developing creativity and intellectual power of early childhood where the material delivered in training is ,